219k views
5 votes
AP CAL AB!!!! HELP!!

AP CAL AB!!!! HELP!!-example-1

1 Answer

2 votes

Answer:

1)
f'(x)= (3)/(2√(3x-5))

2)
y=(3)/(4)x-(1)/(4)

Explanation:

So we have the function:

1)

And we want to find its derivative using the limit definition:


\lim_(h \to 0) (f(x+h)-f(x))/(h)

So, let's do so:


\lim_(h \to 0) (√(3(x+h)-5)-√(3x-5))/(h)

Simplify the first square root:


\lim_(h \to 0) (√(3x+3h-5)-√(3x-5))/(h)

Now, let's remove the square root by multiplying by its conjugate. So:


\lim_(h \to 0) (√(3x+3h-5)-√(3x-5))/(h)\cdot (( √(3x+3h-5)+√(3x-5) )/(√(3x+3h-5)+√(3x-5) ))

In the numerator, difference of two squares. In the denominator, multiply:


\lim_(h \to 0) ((3x+3h-5)-(3x-5))/(h(√(3x+3h-5)+√(3x-5)))

Distribute the numerator:


\lim_(h \to 0) ((3x+3h-5)-3x+5)/(h(√(3x+3h-5)+√(3x-5)))

Simplify:


\lim_(h \to 0) (3h)/(h(√(3x+3h-5)+√(3x-5)))

Cancel out the h:


\lim_(h \to 0) (3)/(√(3x+3h-5)+√(3x-5))

Direct substitution:


= (3)/(√(3x+3(0)-5)+√(3x-5))

Simplify:


= (3)/(√(3x-5)+√(3x-5))

Combine like terms:


= (3)/(2√(3x-5))

Therefore:


f'(x)= (3)/(2√(3x-5))

Your answer is indeed correct!

2)

Now, let's find the equation of the tangent line to the graph at x=3.

Remember what the derivative gives us. The derivative tells us the slope of the tangent line to a graph at a certain point. So, let's substitute 3 into f'(x) to find the slope of our tangent line:


f'(3)= (3)/(2√(3(3)-5))

Multiply and subtract:


f'(3)= (3)/(2√(9-5))\\f'(3)= (3)/(2√(4))

Simplify:


f'(3)= (3)/(2(2))\\f'(3)= (3)/(4)

Therefore, the slope of our tangent line is 3/4.

Now, let's find the equation of the line using the point-slope form. So, we need to point at x=3 of the original graph. So, substitute 3 into the original function:


f(3)=√(3(3)-5)

Multiply, subtract, and simplify:


f(3)=√(9-5)\\f(3)=√(4)\\f(3)=2

Therefore, our point is (3,2).

Now, we can use the point-slope form, where:


y-y_1=m(x-x_1)

Let (3,2) be (x₁, y₁) and substitute 3/4 for m. Therefore:


y-2=(3)/(4)(x-3)

Distribute:


y-2=(3)/(4)x-(9)/(4)

Add 2 to both sides:


y=(3)/(4)x-(1)/(4)

And we're done!

User Torbatamas
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.